DIGITAL TRANSFORMATION OF THE CUSTOMS SPHERE IN THE CONDITIONS OF THE FORMATION OF THE DIGITAL SPACE OF EAEU - A. V. Shimanskaja (Цифровая трансформация, 2018)
The role of digital transformation in the general picture of the formation of the digital space of EAEU is analyzed. The main world trends, which testify to the process of introduction of digital technologies in the customs sphere, are also highlighted. It is given the assessment of the existence of such trends in EAEU as the development of preliminary information, electronic declaration (including automatic release of goods), the mechanism of "Single Window". The model of the process of automatic customs clearance is proposed. The main emphasis is put on the development of digital trading platforms based on Single Window systems. The examples of construction of digital platforms providing the concept of continuous paperless trade are considered. The leading role of the Integrated Information System of EAEU was noted as the basis of the digital platform in the construction of the digital space of EAEU. Intensive development and implementation of the national Single Window systems in the EAEU member states were proposed as necessary elements for the full operation of the Integrated Information System, as well as the unification of information resources in the customs sphere into the single digital trading platform of EAEU.